The Effectiveness of Quick Response Code-based Career Profession Media to Enhance Students Career Insights - Ayu, Ega; Sugiyo, Sugiyo; Japar, Muhammad (Universitas Negeri Semarang, 2023)
Secondary school level is a strategic level in which a human must improve his knowledge or insights about a future profession and career planning. Thus, the present study strived for examining the effectiveness of quick response code-based career profession cards to enhance the insights of eight graders. The students’ data were collected using a career insights scale and further analyzed using paired sample statistic test and paired sample t-test. Following the analysis, there was an effect of quick response code-based career profession cards on the improvement of eight graders career insights. Therefore, the medium of quick response code-based career profession cards needs to be utilized to enhance students’ career insights.